2012
DOI: 10.1007/s11130-012-0283-3
|View full text |Cite
|
Sign up to set email alerts
|

Potato- An Important Source of Nutritional Kynurenic Acid

Abstract: Kynurenic acid (KYNA) is a metabolite of tryptophan which is formed along the kynurenine pathway. KYNA may possess neuroprotective, anti-inflammatory, antioxidant and antiproliferative properties. This study measured the concentration of KYNA in various varieties of potatoes and products made from potatoes. KYNA content was determined by means of the high-performance liquid chromatography with fluorescence detection. KYNA was found in all 16 studied varieties of potato tubers in amounts varying from 0.239 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
0
33
1
Order By: Relevance
“…This metabolite is produced from the oxidative conversion of tryptophan to the intermediate kynurenine, which is further transformed to kynurenate. Kynurenate is a potent antioxidant (Lugo‐Huitrón et al, ) and has been detected in a diverse range of plants including medicinal herbs, broccoli, and potato (Turski et al, ; Turski, Kamiński, Zgrajka, Turska, & Turski, ). The activation of the tryptophan/kynurenate pathway is supported by covariation with xanthurenic acid (Figure a), which is also derived from the kynurenine intermediate, and oxo‐glutarate (Figure c), which is a cosubstrate in the kynurenate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This metabolite is produced from the oxidative conversion of tryptophan to the intermediate kynurenine, which is further transformed to kynurenate. Kynurenate is a potent antioxidant (Lugo‐Huitrón et al, ) and has been detected in a diverse range of plants including medicinal herbs, broccoli, and potato (Turski et al, ; Turski, Kamiński, Zgrajka, Turska, & Turski, ). The activation of the tryptophan/kynurenate pathway is supported by covariation with xanthurenic acid (Figure a), which is also derived from the kynurenine intermediate, and oxo‐glutarate (Figure c), which is a cosubstrate in the kynurenate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest concentration of KYNA, on the other hand, was found in various kinds of meat, including pork, beef and fish. The content of KYNA in vegetables with the highest content of KYNA was 100× higher in comparison to the content of KYNA in studied meat (Turski et al., , ).…”
Section: Discussionmentioning
confidence: 87%
“…KYNA was isolated and determined according to the methods described previously (Shibata, ; Turski et al., ). Samples were applied to the columns containing cation exchange resin Dowex 50 and the fraction containing KYNA was eluted.…”
Section: Methodsmentioning
confidence: 99%
“…The most recent studies by our group have revealed the antiproliferative activity of kynurenic acid, another endogenous tryptophan metabolite, towards cancer cells, including colon cancer cells (Walczak et al, 2011(Walczak et al, , 2012a. Kynurenic acid was found in human body fluids (Kuc et al, 2006(Kuc et al, , 2008Paluszkiewicz et al, 2009;Walczak et al, 2011) as well as in variety of plant and honeybee derived foodstuffs (Turski et al, , 2012Zgrajka et al, 2013). When administered intragastrically, it was absorbed and transported into the peripheral organs, where it was found in concentrations exerting antiproliferative activities in vitro Walczak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%